Exploring stable between-person and dynamic within-person relations between illegitimate tasks and employee wellbeing. - Stein, Maie; Zacher, Hannes; Rudolph, Cort W.; Semmer, Norbert K. (Work & Stress)
Drawing on stress-as-offense-to-self (SOS) theory and dynamic stressor-strain perspectives, we develop and test a model of reciprocal relations between illegitimate tasks and employee wellbeing. Across two preregistered longitudinal studies with n = 1,734 and n = 1,037 employees, we examine how illegitimate tasks and negative affect as well as physical and mental health are related to one another over time. Random intercept cross-lagged panel models indicated that illegitimate tasks were positively related to negative affect and negatively related to physical and mental health at the between-person level of analysis. The assumed within-person dynamics were partially supported. In Study 1, unreasonable tasks were positively associated with high-activated negative affect over the following six months, and vice versa. In Study 2, illegitimate tasks were positively related to next-month anger, depression, and fatigue and negatively related to next-month physical health. Furthermore, anger was positively related to next-month illegitimate tasks, whereas anxiety unexpectedly predicted reduced unnecessary tasks. Overall, evidence for associations between unreasonable tasks and wellbeing was stronger compared to unnecessary tasks. These findings advance the understanding of the directionality of relations between illegitimate tasks and impaired wellbeing and suggest the need for future research to account for dynamic, within-person relations among these variables.